Estimating Biogenic Silica Production of Rhizaria in the Global Ocean. Issue 3 (2nd March 2020) - Llopis Monferrer, Natalia; Boltovskoy, Demetrio; Tréguer, Paul; Sandin, Miguel Méndez; Not, Fabrice; Leynaert, Aude
Abstract: Siliceous polycystines and phaeodarians are open‐ocean planktonic protists found throughout the water column and characterized by complex siliceous skeletons that are formed, at least partly, through the uptake of silicic acid. These protists contribute to the marine organic carbon (C) and biogenic silica (bSi) pools, but little is known about their contribution to the silica (Si) biogeochemical cycle. Here we report the first measurements of the Si uptake rate of polycystine and phaeodarian cells from samples collected in the Mediterranean Sea using the 32 Si‐based method. The elementary composition (bSi, particulate organic carbon and nitrogen) of these organisms was also measured. Combining our results with published data on the distribution and abundance of Polycystina and Phaeodaria in the global ocean, we conclude that these organisms could contribute from 0.2 to 2.2 mmol Si m −2 of the marine standing stock of bSi and from 2 to 58 Tmol Si yr −1 (1% to 19%) of the global oceanic biogenic silica production. The implications for the global marine Si cycle are discussed. Key Points: Polycystines and phaeodarians are highly silicified cells (up to 11.6 μmol bSi mm −3 ) Over a large size spectrum, Si content of these siliceous rhizarians is associated with their cell size These protists are able to consume dissolved Si and could contribute from 1% to 19% of the biogenic silica production of the global ocean